1999
DOI: 10.1101/gad.13.6.655
|View full text |Cite
|
Sign up to set email alerts
|

Translational induction of heat shock transcription factor sigma 32: evidence for a built-in RNA thermosensor

Abstract: Induction of heat shock proteins in Escherichia coli is primarily caused by increased cellular levels of the heat shock -factor 32 encoded by the rpoH gene. Increased 32 levels result from both enhanced synthesis and stabilization. Previous work indicated that 32 synthesis is induced at the translational level and is mediated by the mRNA secondary structure formed within the 5-coding sequence of rpoH, including the translation initiation region. To understand the mechanism of heat induction of 32 synthesis fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
260
0
3

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 271 publications
(266 citation statements)
references
References 41 publications
(42 reference statements)
3
260
0
3
Order By: Relevance
“…3, one might consider overexpression of 32 to be at the basis of high pressure resistance in the MG1655 mutants, particularly in LMM1030. It should be taken into account, however, that 32 mRNA is not readily accessible for the translational apparatus due to secondary structures that can be resolved by heat (37,38). Consequently, because these mutants are pressure resistant without heat shock induction, an additional mechanism must be active.…”
Section: Discussionmentioning
confidence: 99%
“…3, one might consider overexpression of 32 to be at the basis of high pressure resistance in the MG1655 mutants, particularly in LMM1030. It should be taken into account, however, that 32 mRNA is not readily accessible for the translational apparatus due to secondary structures that can be resolved by heat (37,38). Consequently, because these mutants are pressure resistant without heat shock induction, an additional mechanism must be active.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the ability of ribosomal subunits to recognize this region could be heat enhanced, presumably through thermal destabilization of the stem. This model draws by analogy on studies that have elucidated a mechanism of bacterial heat shock preferential translation (28,31). In that instance, a series of studies have shown that thermal melting of a stem-containing region including the Shine-Dalgarno region, and perhaps also a downstream box segment, allows rRNA base-pairing and ribosome recruitment only at elevated (heat shock) temperatures (28,31).…”
Section: Figmentioning
confidence: 99%
“…This model draws by analogy on studies that have elucidated a mechanism of bacterial heat shock preferential translation (28,31). In that instance, a series of studies have shown that thermal melting of a stem-containing region including the Shine-Dalgarno region, and perhaps also a downstream box segment, allows rRNA base-pairing and ribosome recruitment only at elevated (heat shock) temperatures (28,31). Whereas we do not yet have any direct evidence that a similar mechanism applies to Hsp90 mRNA translation in Drosophila, the concept that a prokaryotic mechanism of preferential translation might be retained as the foundation for a lower eukaryote is intriguing.…”
Section: Figmentioning
confidence: 99%
“…In response to a sudden increase in temperature or other stresses, the levels of σ$# rise transiently because of increased synthesis and protein stabilization. The induction of synthesis is mainly mediated by relief of translational repression due to a secondary structure in the mRNA (Morita et al, 1999 ;Nagai et al, 1991 ;Yuzawa et al, 1993), though the level of rpoH transcription also increases slightly (Erickson et al, 1987 ;Tilly et al, 1986). Stabilization occurs with the release of σ$# from a DnaK\DnaJ\GrpE chaperone complex as DnaK binds denatured proteins generated under stress conditions (Gamer et al, 1996).…”
Section: Introductionmentioning
confidence: 99%